Effect of Copper Slag in Subgrade Soil for Design of Flexible Runway Pavement - Vanshika (My University, 2018)
Preparation of subgrade for a transportation infrastructure on a problematic soil like clayey soil has always been a matter of great concern as clay can exhibit geotechnical problems like high compressibility, high plasticity, high swelling and shrinkage properties etc. To solve these problems and to improve the quality of soil, various soil stabilisation methods can be used. In our study, the properties of the clayey soil is improved by mixing the soil with industrial wastes like copper slag. Use of copper slag is done as it is way more cost effective and eco friendly options than others. The copper slag was collected from SYNCO industries, Jodhpur, Rajasthan and it was used to investigate the effect on locally available soil from Rajpura, Patiala, Punjab. Various proportions of copper slag (10%, 20%, 30%, 40%, 50%, 60% by weight of the parent soil) was used. The strength of the soil was observed by performing compaction tests, CBR tests etc. The observation of CBR tests explored that the CBR of the soil increases with increase in percentage of copper soil and hence the mix can be successfully used as a subgrade for flexible pavement for airport. FAARFEILD computer program is used to determine the pavement layer thickness.
Master of Engineering- Infrastructure
Keywords: Copper Slag; Subgrade Soil; Flexible Runway Pavement